2017
DOI: 10.1007/978-3-319-52280-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Point-Spread-Function-Aware Slice-to-Volume Registration: Application to Upper Abdominal MRI Super-Resolution

Abstract: Abstract. MR image acquisition of moving organs remains challenging despite the advances in ultra-fast 2D MRI sequences. Post-acquisition techniques have been proposed to increase spatial resolution a posteriori by combining acquired orthogonal stacks into a single, high-resolution (HR) volume. Current super-resolution techniques classically rely on a two-step procedure. The volumetric reconstruction step leverages a physical slice acquisition model. However, the motion correction step typically neglects the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Fig. 2 presents a visual comparison of three methods for fetal brain segmentation applied to Group B1 and Group B2 respectively: 1) Salehi et al 2 [10], applying the U-Net to the whole input image for segmentation without a localization stage, 2) P-Net (S) trained with the basic Dice loss function (at a single scale), and 3) P-Net (S) + ML where P-Net (S) was trained with our proposed multi-scale loss function. Both P-Net (S) and P-Net (S) + ML were applied to the output of P-Net (L).…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2 presents a visual comparison of three methods for fetal brain segmentation applied to Group B1 and Group B2 respectively: 1) Salehi et al 2 [10], applying the U-Net to the whole input image for segmentation without a localization stage, 2) P-Net (S) trained with the basic Dice loss function (at a single scale), and 3) P-Net (S) + ML where P-Net (S) was trained with our proposed multi-scale loss function. Both P-Net (S) and P-Net (S) + ML were applied to the output of P-Net (L).…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…≥ σ containing only slices in high agreement with their simulated counterparts projected from the previous HR iterate according to a similarity measure Sim and parameter σ > 0. α ≥ 0 denotes a regularization parameter and ∇ the differential operator. We thus have a convex SRR problem with complete outlier removal in a linear leastsquares formulation that is efficiently solvable using matrix-free operations [2].…”
Section: P-net (L)mentioning
confidence: 99%
“…Our preliminary study demonstrated the feasibility of upper abdominal MRI SRRs generated from only two standard MRCP protocol axial and coronal SST2W series using HT2W volumes as a reference‐guide for in‐plane deformable slice‐to‐volume (S2V) registration/motion correction. but anatomical clarity was lacking and a more robust registration/motion correction was needed.…”
Section: Introductionmentioning
confidence: 91%
“…The axial and the coronal MR images are first corrected for bias field effects [17]. In order to compensate for the highly anisotropic resolution of clinical MR images (up to a factor of 10), we combine both MR acquisitions into a 1×1×1 mm 3 resolution image using the SRR algorithm presented in [18]. To ease the subsequent registration, the CT is also resampled to the same resolution using a cubic interpolation scheme.…”
Section: Pipeline For Automated Segmentationmentioning
confidence: 99%